Beyond ‘greeting’ and ‘thanking’: politeness in job interviews - Tan, H. K.; Teoh, M. L.; Tan, S. K. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Despite the steps taken by Malaysian institutions of higher learning to equip their graduates with the necessary communication skills, local graduates are still failing to create a positive impression on the employers especially during job interviews. Hence this study explored the face-related concept of politeness proposed by Brown and Levinson (1999) at job interviews. Eight final-year undergraduates taking a communication for employment course volunteered for a mock-interview session with a human resource manager from the banking industry. The interviews were audio- and video-recorded and subsequently transcribed. Then a micro-analysis of the data was carried out using Brown and Levinson’s (1999) framework to identify the politeness strategies that the candidates used. Two positive politeness strategies were identified, the first is noticing and attending to interviewer’s interests, wants, needs or goods, and second is raising/asserting common grounds to establish solidarity. One negative politeness strategy was identified which is requesting for clarification or repetition. The pedagogical implications of these findings will be discussed and recommendations for teaching face-related politeness in communication for employment courses will be offered.